Cardiovascular Autonomic Profile in Women With Premenstrual Syndrome - Koifman, Rimma; Dayan, Lior; Ablin, Jacob N.; Jacob, Giris (Frontiers in Physiology, 2018)
Introduction: The premenstrual syndrome (PMS) is a constellation of somatic and psychogenic symptoms that appear during late luteal (LL) phase of the menstrual cycle. Since many symptoms could be related to the autonomic nervous system, we hypothesized that the sympathetic nervous system is perturbed in PMS. Methods: The cardiovascular autonomic profile of nine women with PMS (30.4±2.5 years) were compared to that of nine healthy controls (30±2.5 years) during their early follicular (EF) and LL phases of the menstrual cycle. Plasma norepinephrine (NE) concentrations, power spectral analysis of heart rate (HR) and systolic blood pressure (BP), and baroreflex sensitivity (BRS) were assessed during recumbency and a head-up tilt (HUT). Cardiovascular responsiveness to α1- and β-adrenoreceptor agonists (phenylephrine and isoproterenol, respectively) were also assessed. Results: In the LL phase, the plasma NE concentrations in women with PMS during recumbency and a HUT were lower than those in women without PMS (180±30 vs. 320±50 pg/ml; p=0.04 (recumbent), and 480±70 vs. 940±180 pg/ml: p=0.02 (HUT)). In the LL phase, the dose of phenylephrine required to increase systolic BP by 15 mm Hg in women with PMS was significantly greater than that in women without PMS (202±30 µg versus 138±20 µg; p=0.02). Sympathetic and vagal cardiac control indices were comparable in the two groups in the menstrual phases. In women with PMS, the value of LFSBP in the LL phase was lower than that in the EF phase (0.98±0.2 vs. 1.77±0.4 mmHg2, p=0.04). The increase in LFSBP in women with PMS in the LL phase during HUT was greater than that in the controls, 5.2±0.9 vs. 3.1±0.5 mmHg2, p=0.045, and this increase was associated with a significant decrease in baroreflex sensitivity (BRS). Conclusion: In women with PMS without psychogenic symptoms, the sympathetic control of their circulation is not dominant during the LL phase of their menstrual cycle.